Teachers’ Strategies in Preparing Online Learning Digital Media for Developing Children’s Literacy Skills - Hazizah, Nur; Ismaniar, Ismaniar (Universitas Negeri Semarang, 2020)
The era of 4.0, following the advancement of technology especially digital media, has challenged the existed learning activity of kindergarten students. Due to the pandemic situation, learning activity must be conducted from home. Hence, this research aims to observe the teachers’ strategies in preparing digital media to develop children’s literacy skills during online learning. This research used a quantitative approach using the survey method. Findings showed that 90.48% of teachers have planned their strategies properly to develop children’s literacy skills using digital media. Meanwhile from the implementation, 45.24% was not conducted optimally, and from the evaluation, only 53.28% of the children have developed their literacy skills using digital media in online learning. The benefit of this research is to provide an explanation that education in the pandemic era must prioritize coordination between teachers, parents and their children.